Pemanfaatan Energi Baru Terbarukan Berbasis PLTS Area Pertanian dan Area Tunel Garam Tloglopragoto, Mirit, Kabupaten Kebumen - Akhmad Fadjeri; Aulia Rahmawati; Rasyid Zuhdi; Farsellia Farsellia; Fahmi Fachri; Anisa Lutfiyani; Taufik Hidayat; Anisa Dwi Nurchayati; Tri Anggoro; Khoerul Anam (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2026)
Tlogopranoto Village, Kebumen Regency, is a cayenne pepper producing area with the main challenge of sandy soil conditions on the south coast, which causes water to evaporate quickly and be absorbed. This condition requires more intensive irrigation, which has been relying on conventional electricity at a high cost. To overcome this challenge and support the sustainability of production, a community service programme through KOSABANGSA from Ma'arif Nahdlatul Ulama University of Kebumen and AKPRIND University of Indonesia introduced Appropriate Technology (TTG) in the form of a Solar Power Plant (PLTS) for sprinkle irrigation systems on a one-hectare chilli field. This solar power plant reduces dependence on fossil energy, saves operational costs, and supports environmentally friendly agricultural practices by relying on renewable energy. The programme also included digital marketing counselling to the farmer group Gapoktan Krajan in Tlogopranoto Village. This counselling provided farmers with skills in using social media and e-commerce to expand the market for their products. In addition, training on solar power plant maintenance ensures the continued use of an efficient solar-powered irrigation system. The results of this programme show an increased capacity of farmers in managing modern irrigation technology and digital marketing, which is expected to increase their productivity and income. Overall, the implementation of solar PV as an irrigation solution is a clear example of the application of sustainable technology in the agricultural sector, supporting climate change mitigation efforts and the achievement of Sustainable Development Goals (SDGs) targets.